Design Adventure Education Mathematics Game to Improve The Ability of Creative Thinking in Mathematics - Kartika, Yessi; Wahyuni, Rahmi; Sinaga, Bornok; Rajagukguk, Juniastel (International Journal for Educational and Vocational Studies, 2020)
The very rapid development of technology is slowly appearing in the world of education. Educational games are a form of multimedia that packages learning programs in the form of games, so besides being games, they are also educational. The use of game education technology as an interactive learning medium is one of the right ways to improve students' mathematical creative thinking skills. This educational game is expected to eliminate the feeling of boredom and fear of learning mathematics and can facilitate the learning process on geometry material for Senior High School (SMA)/Islamic Senior High School (MA). This study aims to develop an Android-based educational game that can be operated on various smartphones with the Android operating system and to test the feasibility of using adventure games as a medium for learning geometry. This game can be used as an alternative medium for learning geometry in changing conventional learning methods to learning game simulations, so as to improve students' mathematical creative thinking abilities, because in educational games it has elements of challenge, accuracy, reasoning and ethics. The methodology used in this research is the research development method or Research and Development (R & D) using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model with the following activity stages: (1) Analysis, gathering information; (2) Design, designing multimedia-based animation media and validating media designs; (3) Development, improvement of media design; (4) Implementation, media testing; (5) Evaluation, product revision.